Modal Sosial Etnis Tionghoa Dalam Perekonomian Di Masyarakat - Ciek Julyati Hisyam; Chieka Aisyah Kinanti; Alma Miftaqiyah; Sylmi Adila (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
This article discusses the analysis of social capital of the Chinese ethnic group in the economy of Indonesian society, referring to the social capital theory of Robert D. Putnam. Social capital, which includes social networks, trust, and collective efficacy, plays a significant role in the economic success of the Chinese community in Indonesia. Through case studies and theoretical analysis, this article highlights how strong social networks, reputation, and credibility assist the Chinese community in sustaining their businesses and adapting to economic and social changes.